The efficacy of the theory of planned behaviour and value-belief-norm theory for predicting young Chinese intention to choose green hotels - Qi Zhang; Philip Pong Weng Wong; Lei Wang (Scientific Reports)
Abstract Although hotels have begun to pay more attention to green practices in providing products and services to satisfy guests’ green needs, the percentage of guests visiting green hotels is still low. Researchers undervalue the connection between consumers’ values, attitudes, norms, and intentions to stay at green hotels. Recently, scholars suggested that the attitude-intention gap can be closed by combining the theory of planned behaviour and the value-belief-norm theory. Therefore, this study examined the interrelationships among various constructs based on both theories. A total of 406 university students from Xuzhou City, China were employed quantitatively, utilising a purposive sample technique to test hypotheses using the Statistical Package for the Social Sciences and structural equation modelling. The results demonstrated that altruistic value, biospheric value, and collectivistic value positively influenced ecocentric attitude respectively. Implicit attitude was positively influenced by biospheric value, collectivistic value, and ecocentric attitude. Meanwhile, ecocentric attitude positively influenced awareness of consequence, subsequently ascription of responsibility, then the personal norm, and finally intention. Furthermore, implicit attitude, subjective norm, and perceived behavioural control positively influenced intention separately while subjective norm favourably influenced implicit attitude, perceived behavioural control, and personal norm respectively. The findings of this study would significantly contribute to a deeper understanding of consumers’ green hotel visits based on a combined theoretical framework from a developing country with a highly collectivistic value orientation, which benefits the growth of the green hotel industry and other key stakeholders.